Public Relations Content Strategy Innovation for the Image of Regional Heads in the Digital Era of East Java - Joko Bramono Susilo; Nur Annafi (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study aims to analyze the innovation of public relations (PR) content publication strategies in shaping the image of regional leaders in East Java Province, focusing on the utilization of digital technology. The main issue addressed is the lack of effectiveness of content strategies in changing public perception and building a positive image. Using the theories of relations, reputation, and relevance (Onggo, 2004), the study explores and analyzes how PR content strategies can be innovatively applied. The research employs a qualitative method with a case study approach, involving in-depth interviews and document analysis. The findings indicate that the use of social media and digital platforms enhances two-way communication, strengthens relationships, and builds a positive reputation. Relevant and timely content increases public engagement, ensuring government messages remain significant. The study suggests optimizing digital technology and enhancing PR staff training to master the latest digital tools. Recommendations for future research include comparative studies across regions on the effectiveness of digital communication strategies. Thus, this study provides practical and theoretical insights to improve the effectiveness of public communication in the digital era, supporting the success of programs and policies in East Java Province.